2012
DOI: 10.1177/003335491212700316
|View full text |Cite
|
Sign up to set email alerts
|

On Linkages; Using GIS for Administrative Decision-Making in a Local Public Health Setting

Abstract: Articles for From the Schools of Public Health highlight practice-and academic-based activities at the schools. To submit an article, faculty should send a short abstract (50-100 words) via e-mail to Allison Foster, ASPH Deputy Executive Director, at afoster@asph.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Moreover, the newly established hospitals did improve the inhabitants' geographical access over the period of study. Lack of geographical access to such services has been observed in similar studies such as the one conducted in Alabama and Kentucky, United States of America (27), which revealed that a 22.9% drop in mortality rates was a direct result of improved availability and accessibility to healthcare services. In addition, the study pointed out that mortality rates were not only a result of demographic characteristics (28), but inequity might have also affected the epidemic patterns of disorders and might have resulted in unexpected events (29).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, the newly established hospitals did improve the inhabitants' geographical access over the period of study. Lack of geographical access to such services has been observed in similar studies such as the one conducted in Alabama and Kentucky, United States of America (27), which revealed that a 22.9% drop in mortality rates was a direct result of improved availability and accessibility to healthcare services. In addition, the study pointed out that mortality rates were not only a result of demographic characteristics (28), but inequity might have also affected the epidemic patterns of disorders and might have resulted in unexpected events (29).…”
Section: Discussionmentioning
confidence: 65%
“…The age group of > 65 years experienced an upward trend of non-accessibility from 4.70% in 1997 to 5.38% in 2007, yet witnessed a downward trend from 5.38% in 2007 to 4.84% in 2012 (Table 1 and Figure 2). Possible explanations for this include: 1) reducing age group population; 2) migration of young and middle-age groups city centre areas where most hospitals are located, to areas without access according to our criteria (32); and 3) geographical access to healthcare services is a high priority for the elderly population of the target community; the results of studies performed in the United States and Spain demonstrated that the elderly population had a tendency to live in the immediate vicinity of medical facilities (27,33). Furthermore, in another study it was shown that long travel intervals between the place of residence for the elderly and medical centres created substantial physical obstacles for them (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, Taylor et al [87] argue that the use of GIS as a tool to determine where clinics can be placed to maximise access to care is particularly relevant for primary care services associated with ongoing changes to the health system, especially in light of the Patient Protection and Affordable Care Act 2010. The study by Taylor et al is important because it demonstrates a way in which GIS can be used for administrative decision-making at the local public health level.…”
Section: Resultsmentioning
confidence: 99%
“…When linked with publicly available health information, which is becoming more and more plentiful, 50 this method has tremendous potential to inform health administration and community advocacy. 48,51 The types of spatial and health data used in this study are widely available, an important factor in policy-relevant research.…”
Section: Discussionmentioning
confidence: 99%